Modified basalt fiber, modification method, composite material and preparation method

By grafting cellulose nanofibers on the surface of basalt fibers, and using reduced pressure suction filtration technology to improve the interface bonding between resin and fibers, the problem of poor interface bonding force between basalt fibers and resins is solved, and the mechanical properties of the composite material are significantly improved.

CN119551913AActive Publication Date: 2025-03-04SOUTHWEST PETROLEUM UNIV
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202510113671.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-04
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The poor interface bonding force between basalt fibers and resins leads to the inability to effectively transmit stress when the basalt fiber reinforced resin composite material is subject to external loads, which limits the performance of fiber performance.

Method used

By combining chopped basalt fibers with cellulose nanofibers, the cellulose nanofibers are grafted on the surface of the basalt fibers by using reduced pressure suction filtration technology to provide rich oxygen-containing functional groups and improve the interface bond between the resin and the fiber.

Benefits of technology

The bonding force of the resin-fiber interface is significantly improved and the mechanical properties of the composite material are enhanced, including the improvement of tensile strength and impact strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551913A_ABST
    Figure CN119551913A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses a modified basalt fiber, a modification method, a composite material and a preparation method, and the preparation method comprises the following steps: step 1, crushing chopped basalt fibers until the average length is 1 mm, cleaning and drying to obtain chopped basalt fiber powder; step 2, uniformly laying the chopped basalt fiber powder obtained in the step 1 on a water-based filter membrane, and carrying out reduced-pressure suction filtration on the cellulose nanofiber dispersion liquid; step 3, drying the chopped basalt fiber powder obtained in the step 2 to obtain modified basalt fibers; cellulose nanofibers are grafted to the surfaces of the chopped basalt fibers through chemical bonds, the surfaces of the chopped basalt fibers are modified through reduced-pressure suction filtration, and rich oxygen-containing functional groups are provided for the surfaces of the basalt fibers; according to the epoxy resin composite material prepared from the modified short-cut basalt fiber, the binding force of a resin-fiber interface is improved, and the mechanical property of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a modified basalt fiber, a modification method, a composite material and a preparation method thereof. Background Art

[0002] Basalt fiber is made by melting basalt raw materials at 1300~1500℃. Due to the advantages of the material itself being harmless to the environment and the preparation process not requiring the addition of any chemical reagents, it has become a green and environmentally friendly material that has received a lot of research attention in recent years. As a new type of environmentally friendly high-performance inorganic fiber, basalt fiber has high strength and modulus, high and low temperature resistance, and excellent wave absorption. It has received great attention in the automotive industry, aerospace, construction industry and other fields. Compared with long fiber reinforced resin composites, short fiber reinforced resin composites have better ductility, are easy to process and have high production efficiency.

[0003] However, the surface of basalt fiber is smooth and chemically inert, which is very unfavorable for the infiltration between fiber and resin, resulting in poor interfacial bonding between basalt fiber and resin. As a result, when basalt fiber reinforced resin composites are subjected to external loads, stress cannot be better transferred to the reinforcing basalt fiber, and the performance advantages of basalt fiber cannot be fully utilized. Therefore, surface modification of basalt fiber is a key and difficult point in the research of basalt fiber reinforced resin composites.

[0004] In the research of basalt fiber surface modification, common methods include silane coupling agent modification, acid-base etching modification, plasma modification, etc. However, among the above modification methods, there are problems such as low grafting rate of silane coupling agent modification and long reaction time; acid-base etching modifiers have certain pollution to the environment, and plasma modification will damage the fiber itself and reduce the tensile strength of the single fiber. Summary of the invention

[0005] Aiming at the problems existing in the prior art, the present invention provides a modified basalt fiber, a modification method, a composite material and a preparation method.

[0006] The technical solution adopted by the present invention is: a method for modifying basalt fiber, comprising the following steps: Step 1: Crush the chopped basalt fibers to an average length of 1 mm, wash and dry them to obtain chopped basalt fiber powder; Step 2: evenly spread the chopped basalt fiber powder obtained in step 1 on a water filter membrane, and filter the cellulose nanofiber dispersion by vacuum extraction; wherein the mass ratio of the chopped basalt fiber to the cellulose nanofiber is 1:0.06-0.18; Step 3: The chopped basalt fiber powder obtained in step 2 is dried to obtain modified basalt fiber.

[0007] Furthermore, before washing and drying in step 1, the crushed chopped basalt fibers are dispersed in acetone, placed in a Soxhlet extractor, and heated under reflux in a water bath at 80° C. for 24 h.

[0008] Furthermore, the cellulose nanofibers are amino-terminated cellulose nanofibers.

[0009] Furthermore, the modification method of the cellulose nanofibers is as follows: Add NaIO into the cellulose nanofiber dispersion 4 , fully reacted in the dark; cellulose nanofibers and NaIO 4 The mass ratio is 1:2; Add diethylenetriamine and reflux reaction to obtain amino-terminated modified cellulose nanofibers.

[0010] The invention discloses modified basalt fiber obtained by a modification method.

[0011] A method for preparing a composite material based on modified basalt fiber, wherein the modified basalt fiber adopts the modified basalt fiber mentioned above, comprises the following steps: The epoxy resin additive is fully mixed, and the modified basalt fiber is added, wherein the mass of the modified basalt fiber accounts for 2% of the mass of the epoxy resin; The desired composite material can be obtained by ultrasonic stirring at 50 °C and curing after vacuum degassing.

[0012] Furthermore, the additives include a curing agent, an accelerator and an anti-settling agent.

[0013] Furthermore, the curing agent is methyltetrahydrophthalic anhydride, the accelerator is 2, 4, 6-tris(dimethylaminomethyl)phenol, and the anti-settling agent is fumed silica.

[0014] Further, the curing process is as follows: First, cure at 80 °C for 2 h and then at 120 °C for 3 h.

[0015] A composite material based on modified basalt fibers.

[0016] The beneficial effects of the present invention are: (1) The present invention grafts cellulose nanofibers onto the surface of chopped basalt fibers through chemical bonds, and modifies the surface of the chopped basalt fibers by vacuum filtration, thereby providing the surface of the basalt fibers with abundant oxygen-containing functional groups; (2) The epoxy resin composite material prepared by the present invention using modified short chopped basalt fibers improves the bonding strength of the resin-fiber interface and improves the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 These are SEM images of the tensile cross-sections of the epoxy resin composite materials obtained in Example 2 and Comparative Example 1 of the present invention, a and b are the composite materials obtained in Comparative Example 1, and c and d are the composite materials obtained in Example 2.

[0018] Figure 2 This is a Fourier transform infrared spectrum of the chopped basalt fiber before and after modification in Example 2 of the present invention.

[0019] Figure 3 These are the TGA curves of the modified basalt fibers and the basalt fibers before and after modification in Examples 1 to 3 of the present invention.

[0020] Figure 4 These are atomic force microscope images of the modified basalt fibers and the basalt fibers before and after modification in Examples 1 to 3 of the present invention, wherein a is the basalt fibers before modification, b is the modified basalt fibers obtained in Example 1, c is the modified basalt fibers obtained in Example 2, and d is the modified basalt fibers obtained in Example 3.

[0021] Figure 5 The contact angles of the modified basalt fibers and the basalt fibers before and after modification with water and diiodomethane in Examples 1 to 3 of the present invention are shown.

[0022] Figure 6 It is the surface energy of the basalt fiber after modification and the basalt fiber before modification in Examples 1 to 3 of the present invention.

[0023] Figure 7 The tensile strength curves of the epoxy resin composite materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1 are shown.

[0024] Figure 8 The impact strength curves of the epoxy resin composite materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0026] A method for modifying basalt fiber comprises the following steps: Step 1: Crush the chopped basalt fibers to an average length of 1 mm, wash and dry them to obtain chopped basalt fiber powder; before washing and drying, disperse the crushed chopped basalt fibers in acetone, place them in a Soxhlet extractor, and heat and reflux them in a water bath at 80°C for 24 h.

[0027] Step 2: The chopped basalt fiber powder obtained in step 1 is evenly spread on the water filter membrane, and the cellulose nanofiber dispersion is filtered under reduced pressure; wherein the mass ratio of the chopped basalt fiber to the cellulose nanofiber is 1:0.06-0.18; and the cellulose nanofiber is amino-terminated modified cellulose nanofiber. The modification method is as follows: Add NaIO into the cellulose nanofiber dispersion 4 , fully reacted in the dark; cellulose nanofibers and NaIO 4 The mass ratio is 1:2; Add diethylenetriamine and reflux reaction to obtain amino-terminated modified cellulose nanofibers.

[0028] Step 3: The chopped basalt fiber powder obtained in step 2 is dried to obtain modified basalt fiber.

[0029] A method for preparing a composite material based on modified basalt fiber, wherein the modified basalt fiber adopts the modified basalt fiber, comprising the following steps: The epoxy resin additives were fully mixed and modified basalt fibers were added, wherein the mass of the modified basalt fibers accounted for 2% of the mass of the epoxy resin; the additives included a curing agent, an accelerator, and an anti-settling agent. The curing agent was methyltetrahydrophthalic anhydride, the accelerator was 2, 4, 6-tris(dimethylaminomethyl)phenol, and the anti-settling agent was fumed silica. The mass ratio of the curing agent, accelerator, and anti-settling agent to the epoxy resin was 85:1:0.5:100.

[0030] The desired composite material can be obtained by ultrasonic stirring at 50 °C and curing after vacuum degassing.

[0031] The curing process is as follows: First, cure at 80 °C for 2 h and then at 120 °C for 3 h.

[0032] The raw materials used in the following examples are as follows: Chopped basalt fiber BF, length about 3 mm, single fiber diameter about 12 μm; cellulose nanofiber CNF, diameter 50 nm, length 1-3 μm; bisphenol A epoxy resin, E-51; epoxy equivalent 180-200, methyltetrahydrophthalic anhydride (MeTHPA, curing agent) 98%, 2,4,6-tris (dimethylaminomethyl) phenol (DMP-30, accelerator); fumed silica powder (anti-settling agent); acetone: 99.8%, sodium periodate (NaIO 4 ) 99%; ethylene glycol: 98%; triethylenetriamine DETA 99.8%.

[0033] Example 1 First, the chopped basalt fiber was modified according to the following steps: Step 1: Use a wall-breaking machine to break the short-cut basalt fiber into pieces with a length of about 1 mm, put them into a Soxhlet extractor filled with acetone, and heat them in a water bath at 80 °C for reflux for 24 h. Then take them out, wash them, and dry them for 24 h to obtain the short-cut basalt fiber with desizing on the surface, BF.

[0034] Step 2: 0.75 g of BF powder was evenly spread on a water filter membrane (pore size 0.22 μm, diameter 50 mm), and 5 mL of cellulose nanofiber aqueous dispersion was filtered under reduced pressure using a water circulation vacuum pump. The mass of cellulose nanofibers in the cellulose nanofiber aqueous dispersion was 0.06 g.

[0035] Due to the high specific surface energy of CNF nanoparticles as the CNF suspension is filtered during the vacuum filtration process, the CNF nanoparticles will gradually agglomerate, resulting in uneven attachment of CNF to the BF surface. The transmission of stress at the interface between BF and resin will cause stress concentration, which will affect the mechanical properties of the composite material. Therefore, during the vacuum filtration process, a 50 °C water bath is used for heating, and an ultrasonic ultrasonic vibrator is inserted to keep the nanoparticles in a uniformly dispersed state. This is because the ultrasonic action acts on the CNF nanoparticles through the vibration and cavitation effect of sound waves, promoting the dispersion of CNF nanoparticles. The cavitation effect will produce tiny bubbles in the CNF suspension and burst them, generating strong shock waves, which will help the CNF nanoparticles to be more evenly dispersed and maintain a uniform dispersion state in real time during the vacuum filtration process, and enhance the stability of the BF and resin interface.

[0036] During the vacuum filtration process, due to the short length of the chopped basalt fibers, they are evenly dispersed on the filter paper and their surface is not hydrophilic. The CNF suspension can fully contact with the BF, and the droplets remain stable on the surface of the chopped basalt fibers, giving the hydroxyl groups, ether bonds and other functional groups on the CNF surface sufficient contact time with the silanol groups on the BF surface, which provides a guarantee for the formation of hydrogen bonds. When the pressure difference reaches a certain level, the solvent of the CNF suspension is filtered out from the pores of the filter paper, while the CNF is retained on the surface of the chopped basalt fibers.

[0037] When using cellulose nanofibers CNF, the surface is first modified: The cellulose nanofibers are dispersed in deionized water, and the CNFs are evenly dispersed under the action of ultrasound and stirring to prepare an aqueous dispersion with a mass concentration of 1 wt.%.

[0038] Take a water dispersion containing 0.15 g CNF and 0.3 g NaIO 4 In a flask, react at 50 °C in the dark for 12 h, then pour in 30 mL of ethylene glycol to terminate the reaction.

[0039] Adjust the pH to neutral and add 20 mmol of DETA dropwise (add NaIO 4 After that, aldehyde groups will be generated at the ends of CNF structural units. DETA is added to introduce amino groups into the system, which is conducive to Schiff base reaction with aldehyde groups to generate amino-terminated cellulose solution. The solution was refluxed in a water bath with magnetic stirring for 3 h at 40 °C, the pH value was adjusted to neutral, and freeze-dried to obtain amino-terminated modified cellulose nanofibers.

[0040] Step 3: Place in a blast drying oven and dry at 65°C for 4 h to obtain powdered fibers. The fibers obtained in this example are denoted as BF-CNF5.

[0041] The fiber BF-CNF5 obtained in this example is used to prepare an epoxy resin composite material, and the process is as follows: Epoxy resin EP, curing agent, accelerator and anti-settling agent were mixed in a mass ratio of 100:85:1:0.5, and fiber BF-CNF5 accounting for 2 wt.% of the mass of epoxy resin was added, and ultrasonic stirring was carried out at 50 °C for 30 min.

[0042] The mixed solution was placed in a vacuum oven for multiple vacuum degassing. After the solution was completely degassed, it was poured into a mold, placed in an oven and cured according to a gradual temperature increase curing system of 80 °C for 2 h and 120 °C for 3 h. Finally, the obtained composite material was recorded as BF-CNF5 / EP.

[0043] Example 2 The modification method of chopped basalt fiber and the method for preparing epoxy resin composite material in this embodiment are the same as those in Example 1, except that the volume of the cellulose nanofiber aqueous dispersion in step 2 is 10 mL, wherein the mass of the cellulose nanofiber is 0.12 g. The modified chopped basalt fiber obtained is BF-CNF10.

[0044] The epoxy resin composite material prepared by using the same is BF-CNF10 / EP.

[0045] Example 3 The method for modifying chopped basalt fibers and the method for preparing epoxy resin composite materials in this embodiment are the same as those in Example 1, except that the volume of the cellulose nanofiber aqueous dispersion in step 2 is 15 mL, and the mass of the cellulose nanofibers is 0.18 g. The modified chopped basalt fibers obtained are BF-CNF10.

[0046] The epoxy resin composite material prepared by using the same is BF-CNF10 / EP.

[0047] Comparative Example 1 The method for modifying chopped basalt fibers and the method for preparing epoxy resin composite materials in this embodiment are the same as those in Example 1, except that step 2 is not included, and the obtained epoxy resin is recorded as BF / EP.

[0048] Figure 1 Figures 1 and 2 are SEM images of the tensile cross-section of the composite material obtained in Example 2 and Comparative Example 1 of the present invention, a and b are SEM images obtained in Comparative Example 1 at different magnifications, and c and d are SEM images obtained in Example 2 at different magnifications. It can be seen from the figure that in the composite material obtained in Comparative Example 1, the surface of the BF after desizing but not modified is smooth, almost no resin adheres to the fiber surface, and there is an obvious gap between the exposed fiber and the resin matrix. Figure 1 As can be seen in Figure b, there are a large number of holes in the resin matrix of the tensile fracture surface where the fibers are pulled out, which means that there is a poor bond between the fibers and the resin, indicating that the main failure modes of the tensile fracture of BF / EP are fiber debonding and fiber pullout.

[0049] The tensile section of the composite material obtained from Example 2 is: Figure 1 As can be seen in Figure c, the surface of the exposed basalt fiber becomes noticeably rough, the amount of residual resin increases significantly, and the gap between the fiber and the resin decreases significantly. Figure 1 As can be seen in figure d, compared with figure b, the number of holes caused by fiber pullout in the matrix of the resin on the tensile fracture surface is significantly reduced, indicating that CNF-modified basalt fiber has achieved excellent modification effect.

[0050] This is because a large number of hydroxyl groups on the CNF surface form hydrogen bonds with the hydroxyl groups on the BF surface, which not only increases the roughness of the fiber surface, but also provides a large number of active sites on the BF surface. It not only enhances the mechanical interlocking between the fiber and the resin, but also enhances the bonding force between the resin and the fiber during the curing process of the epoxy resin. The chemical structure of chopped basalt fiber does not contain carbon elements and active functional groups, which makes it impossible for the resin to fully wet the surface of the basalt fiber during the curing process, resulting in gaps on the interface. Cellulose nanofibers do not react with the solvent through vacuum filtration, and the chemical structure such as active functional groups is retained. At the interface between the resin and the fiber, the cellulose nanofibers can fully provide active sites, enhance the wetting of the fiber during the resin curing process, and transmit stress when the composite material is subjected to stress.

[0051] The present invention adopts short-cut basalt fiber. The difference between short-fiber reinforced composite material and long-fiber reinforced composite material is that the load does not act directly on the fiber, but on the matrix material, and the load is transferred to the fiber through the fiber end and the fiber surface near the end. CNF and BF are connected by hydrogen bonds and van der Waals forces, resulting in an increase in oxygen-containing active groups on the fiber surface, improving the infiltration of the fiber during the resin curing process, increasing the mechanical interlocking between the resin and the fiber surface, and enhancing the interfacial bonding force of the resin-fiber. When the composite material is subjected to external load, when the stress is transmitted to the resin-fiber interface along the resin matrix, there are a large number of gaps between the unmodified BF and the epoxy resin, which cause a large number of defects inside the composite material, and when the crack is transmitted to the interface, the stress cannot be transmitted to the reinforcing phase fiber, resulting in the fiber pulling out and debonding at the interface, so the mechanical properties of the composite material are poor; and the good interfacial bonding force between the modified resin-fiber will form a stable interfacial phase, and the stress will be transmitted to the reinforcing phase fiber through the interface, and the failure form will change from fiber pulling out and debonding to cohesive failure, thereby achieving the mechanical properties of the composite material.

[0052] Figure 2 The FTIR spectra of the chopped basalt fiber before modification (obtained in step 1) and after modification (obtained in step 3) in Example 2 of the present invention are shown in Figure 1. As can be seen from the figure, the functional groups on the basalt fiber change before and after modification. The BF before modification is at 1284 cm -1 and 857cm -1 The peaks at 3398 cm-1 and 3398 cm-2 correspond to the Si-O-Si and Si-C vibrations of basalt fibers. -1 and 1622cm -1 The stretching vibration peak and bending vibration peak of hydroxyl group were observed at 3427 cm-1. The hydroxyl peak of BF after modification was significantly enhanced and blue-shifted to 3427 cm-1. -1 and 1640cm -1 It is speculated that this is caused by the formation of hydrogen bonds between BF and CNF and the increase of polar groups on the surface of BF.

[0053] The modified BF is at 2931cm -1 and 2858cm -1 -CH 2 The antisymmetric and symmetric stretching vibration peaks, as well as the peaks at 1012 cm -1 The stretching vibration peak of COC was observed. This was because CNF was successfully coated on the BF surface after vacuum filtration and drying. This confirmed that BF was successfully modified by the vacuum filtration of CNF, and thus the corresponding functional groups of CNF could be observed on the BF surface.

[0054] Figure 3 For N 2TGA curves of BF and basalt fibers obtained in Examples 1 to 3 before and after modification after heating from room temperature to 600°C at a heating rate of 10°C / min under atmosphere. Figure 3 The weight loss ratio of BF-CNF varies with the amount of CNF modification at 600 °C. Figure 3 It can be seen that as the temperature rises to 600 ℃, the weight loss of BF reaches 1.05%. Analysis shows that this may be because some sizing agents, some physically adsorbed water and impurities still remain on the BF surface after acetone Soxhlet extraction; but as the CNF content on the BF surface increases by vacuum filtration, the CNF content coated on the BF surface also increases, resulting in an increase in the weight loss of BF-CNFx at 600 ℃, which also confirms that the previous Fourier transform infrared spectrum and SEM image analysis of the tensile section are correct. According to the weight loss of BF-CNFx at 600 ℃, it is calculated that the CNF coating amount on the modified BF surface reached 1.79%, 2.15%, and 2.96%, respectively.

[0055] Figure 4 The atomic force microscope images of the modified basalt fibers and the basalt fibers before modification in Examples 1 to 3 of the present invention are shown in Figure 1. a is the basalt fibers before modification, b is the modified basalt fibers obtained in Example 1, c is the modified basalt fibers obtained in Example 2, and d is the modified basalt fibers obtained in Example 3. It can be seen from the figure that the surface of the unmodified BF is relatively smooth, with a root mean square roughness Rq of 4.920 nm; and after filtering 5 mL of CNF-modified BF surface, it was observed that the BF surface became rougher, and the Rq value increased to 19.747 nm; with the increase of the CNF filtration amount, when it reached 15 mL, Rq increased to 37.496 nm. Compared with the unmodified BF, the surface roughness is significantly improved, and irregular wrinkles are formed on the fiber surface. This is because as the CNF content increases, more and more CNFs are attached to the BF surface through hydrogen bonds, van der Waals forces, etc. Higher surface roughness can promote a stronger mechanical interlocking between the resin and the fiber, thereby enhancing the interfacial bonding force.

[0056] Figure 5 The contact angles of the modified basalt fibers and the basalt fibers before and after modification of Examples 1 to 3 of the present invention with water and diiodomethane. Figure 6The surface energy of the modified basalt fiber and the basalt fiber before modification in Examples 1 to 3 of the present invention. As can be seen from the figure, the contact angles of the unmodified BF and water are about 91.7°, and with the increase of the CNF coating amount, it shows a downward trend, which leads to the increase of the surface energy polar component of the modified BF from 6.82mN / m to 14.83mN / m. This phenomenon is caused by the increase of the CNF coating amount on the BF surface, and the increase of the number of oxygen-containing functional groups on the surface; similarly, the contact angle of the fiber to diiodomethane decreases from 78.8° to 70.89, resulting in a slight decrease in the dispersion component of the fiber surface from 31.41 mN / m to 29.52 mN / m. It is speculated that the uneven coating of CNF on the BF surface is caused by the agglomeration of nanoparticles, which also shows that the coating of CNF slightly increases the roughness of the fiber surface. The surface energy of the fiber increases with the increase of CNF coating amount. Due to the increase in the number of oxygen-containing functional groups on the fiber surface and the improvement of fiber surface roughness, during the curing process of epoxy resin, the resin base liquid can have a better infiltration effect with the fiber, which is more conducive to the mechanical interlocking and physical and chemical effects between the resin and the fiber, thereby improving the bonding strength of the resin-fiber interface and achieving the purpose of improving the mechanical properties of the composite material.

[0057] Figure 7 The tensile strength curves of the epoxy resin composite materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1 are shown. Figure 8 The impact strength curves of the epoxy resin composite materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in the figure. As can be seen from the figure, the tensile strength and impact strength of the BF-CNFx / EP composite material both show a trend of increasing first and then decreasing. The maximum tensile strength is 61.1 MPa in BF-CNF10 / EP, which is an increase of 22.4%; the maximum impact strength is 12.4 kJ / m 2, an increase of 55%. This is because as the CNF content increases, CNF and BF are connected through hydrogen bonds and van der Waals forces, resulting in an increase in oxygen-containing active groups on the fiber surface, which improves the fiber wetting during the resin curing process, increases the mechanical interlocking between the resin and the fiber surface, and enhances the resin-fiber interface bonding force. Combined with the analysis in the introduction, it can be concluded that when the composite material is subjected to external loads, when the stress is transmitted along the resin matrix to the resin-fiber interface, there are a large number of voids between the unmodified BF and the epoxy resin, which cause a large number of defects inside the composite material, and when the crack is transmitted to the interface, the stress cannot be transmitted to the reinforcing phase fiber, resulting in fiber pull-out and debonding at the interface, so the mechanical properties of the composite material are poor; and the good interface bonding force between the modified resin and the fiber will form a stable interface phase, and the stress will be transmitted to the reinforcing phase fiber through the interface. The failure mode changes from fiber pull-out and debonding to cohesive failure, thereby achieving enhanced mechanical properties of the composite material; but with the further increase of CNF content, the tensile strength and impact strength of the composite material have decreased to varying degrees. This is because excessive coating will cause CNF to produce nanoparticle agglomeration at the resin-fiber interface. During the crack transmission process, stress concentration occurs at the interface, resulting in reduced mechanical properties of the composite material.

[0058] The present invention uses the vacuum filtration technology to filter out the solvent of the cellulose nanofiber suspension through filter paper, while the cellulose nanofibers are retained on the surface of the short basalt fibers and form hydrogen bonds with the hydroxyl groups on the surface of the basalt fibers, providing the surface of the basalt fibers with rich oxygen-containing functional groups. The bonding force between the resin and the fibers is enhanced, and the mechanical properties of the composite material are improved. Compared with other modification methods, the vacuum filtration also has the effects of energy saving and low cost, and can be achieved by only using a water circulation vacuum pump; in addition, during the vacuum filtration process, the cellulose nanofiber suspension does not react with the solvent, and no other reaction products appear, so it has a stable modification effect.

Claims

1. A method for modifying basalt fiber, characterized in that: The following steps are involved: Step 1: Crush the chopped basalt fibers to an average length of 1 mm, wash and dry them to obtain chopped basalt fiber powder; Step 2: evenly spread the chopped basalt fiber powder obtained in step 1 on a water filter membrane, and filter the cellulose nanofiber dispersion by vacuum extraction; wherein the mass ratio of the chopped basalt fiber to the cellulose nanofiber is 1:0.06-0.18; Step 3: The chopped basalt fiber powder obtained in step 2 is dried to obtain modified basalt fiber.

2. The method for modifying basalt fiber according to claim 1, characterized in that: In the step 1, before washing and drying, the crushed chopped basalt fibers are dispersed in acetone, placed in a Soxhlet extractor, and heated under reflux in a water bath at 80° C. for 24 h.

3. The method for modifying basalt fiber according to claim 1, characterized in that: The cellulose nanofibers are amino-terminated cellulose nanofibers.

4. The method for modifying basalt fiber according to claim 3, characterized in that: The modification method of the cellulose nanofiber is as follows: Adding NaIO4 to the cellulose nanofiber dispersion and fully reacting in the dark; wherein the mass ratio of cellulose nanofiber to NaIO4 is 1:2; Add diethylenetriamine and reflux reaction to obtain amino-terminated modified cellulose nanofibers.

5. The modified basalt fiber obtained by any one of the modification methods of claims 1 to 4.

6. A method for preparing a composite material based on modified basalt fiber, characterized in that: The modified basalt fiber adopts the modified basalt fiber as claimed in claim 5, comprising the following steps: The epoxy resin additive is fully mixed, and the modified basalt fiber is added, wherein the mass of the modified basalt fiber accounts for 2% of the mass of the epoxy resin; The desired composite material can be obtained by ultrasonic stirring at 50 °C and curing after vacuum degassing.

7. The method for preparing a composite material based on modified basalt fiber according to claim 6, characterized in that: The additives include a curing agent, an accelerator and an anti-settling agent.

8. The method for preparing a composite material based on modified basalt fiber according to claim 7, characterized in that: The curing agent is methyltetrahydrophthalic anhydride, the accelerator is 2, 4, 6-tris(dimethylaminomethyl)phenol, and the anti-settling agent is fumed silica.

9. The method for preparing a composite material based on modified basalt fiber according to claim 7, characterized in that: The curing process is as follows: First, cure at 80 °C for 2 h and then at 120 °C for 3 h.

10. A composite material based on modified basalt fiber obtained by any one of the preparation methods of claims 6 to 9.

Citation Information

Patent Citations

  • Amino-terminated modified cellulose, and preparation method and application thereof

    CN103554510A

  • Flexible graphite alkenyl composite paper and preparation method and application thereof

    CN106968128A

  • Inorganic fiber pellet as well as preparation method and application thereof

    CN114315128A

  • Preparation method of nano-cellulose modified basalt fiber biological filler

    CN115745143A

  • Printing ink and preparation method thereof

    CN115785732A